2013
DOI: 10.1007/s00134-013-3001-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality while on veno-venous extracorporeal membrane oxygenation

Abstract: the authors constructed a very nice model predicting the mortality risk while on veno-venous extra-corporeal membrane oxygenation (vvECMO) in patients with acute respiratory distress syndrome (ARDS) due to H1N1 pneumonia. These patients were analyzed retrospectively from a large Italian vvECMO network [2]. Until publication of this paper, inclusion and exclusion criteria for vvECMO treatment were based on expert opinion [3]. The authors constructed the model from the retrospective data of 60 patients, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Comparison of original and recalibrated estimates revealed considerable differences between the study populations, but continued poor discrimination after recalibration indicated that the combination of predictors was not useful in our study population. The ECMOnet score has been externally validated twice in patient populations with a similar profile as the original study [6,14]. Recent results indicate that patients receiving ECMO due to influenza-A virus infection have a lower mortality than patients presenting with other causes of ALF [13].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of original and recalibrated estimates revealed considerable differences between the study populations, but continued poor discrimination after recalibration indicated that the combination of predictors was not useful in our study population. The ECMOnet score has been externally validated twice in patient populations with a similar profile as the original study [6,14]. Recent results indicate that patients receiving ECMO due to influenza-A virus infection have a lower mortality than patients presenting with other causes of ALF [13].…”
Section: Discussionmentioning
confidence: 99%